2019
DOI: 10.1002/nau.24002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of delay elimination communication on the prevalence of primary nocturnal enuresis—a survey from Mainland China

Abstract: Aims A pilot survey shows that primary nocturnal enuresis (PNE) prevalence has increased significantly during the past decade in Mainland China. Whether it is related to the delay of elimination communication (EC) is unclear. This study retrospectively investigated the influence of delayed EC on the PNE prevalence in children and adolescents in mainland China. Methods A cross‐sectional study of PNE prevalence was performed by distributing 19 500 anonymous self‐administered questionnaires to parents in five pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…However, compared to the findings of the 2005 study in Xi'an, our sample's prevalence of NE was lower, 3.99%. This lower prevalence might have been due to improvements in income, parental occupation, parental education level, and living habits [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, compared to the findings of the 2005 study in Xi'an, our sample's prevalence of NE was lower, 3.99%. This lower prevalence might have been due to improvements in income, parental occupation, parental education level, and living habits [9].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that with the widespread use of DD, younger children had used it much longer than the older (Supplementary Table 3, Additional File 1). Due to increases in income, parents may prolong the use of DD and delay toilet training, thus promoting the occurrence of NE [9]. Joinson et al [27] suggested that delayed toilet training (after 24 months) was likely to induce persistent urine accidents during the daytime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many potential risk factors of OAB in children remain unclear. The effect of the elimination communication (EC) start time on NE has recently been reported . EC is an infant‐led, caregiver‐operated practice that helps infants to gradually develop self‐controlled urination and defecation.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the elimination communication (EC) start time on NE has recently been reported. 6 EC is an infant-led, caregiver-operated practice that helps infants to gradually develop self-controlled urination and defecation. In detail, a caregiver uses the infant's cues or natural timing, or transitions and intuition to recognize when the child needs to eliminate; the caregiver then teaches the infant to eliminate in a potty, toilet or any other appropriate place at predictable times and in a gentle position.…”
Section: Introductionmentioning
confidence: 99%